2020
DOI: 10.1097/md.0000000000022683
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of left ventricular end diastolic pressure in patients with diastolic heart failure

Abstract: To evaluate the left ventricular end diastolic pressure (LVEDP) in patients with diastolic heart failure by echocardiography and explore the clinical value of echocardiography. From July 2017 to January 2018, 120 patients were prospectively selected from the affiliated hospital of Jiangsu university diagnosed as diastolic heart failure (York Heart Association class ≥II, LVEF ≥50%). The patients were divided into group with LVEDP ≤15 mm hg (1 mm hg = 0.133 kpa) (43 cases) and the group with LVEDP >15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…Among them, the main judgment indexes of DHF determined by Doppler ultrasound include E /Ea > 8, LVEDP > 15 mmHg, and LVEF > 50%. The results of other studies showed that the decrease of LVEDD, Vp, and LVEF was the factor of DHF produced [ 18 , 19 ]. Other studies have shown that Vp < 45 cm/s is the left ventricular diastolic dysfunction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the main judgment indexes of DHF determined by Doppler ultrasound include E /Ea > 8, LVEDP > 15 mmHg, and LVEF > 50%. The results of other studies showed that the decrease of LVEDD, Vp, and LVEF was the factor of DHF produced [ 18 , 19 ]. Other studies have shown that Vp < 45 cm/s is the left ventricular diastolic dysfunction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Therefore, it is of great significance to evaluate the left ventricular diastolic function of patients with APE in clinical practice. At present, studies have confirmed that echocardiography can effectively evaluate the left ventricular diastolic function of patients with metabolic syndrome, 7 diastolic heart failure, healthy adults, 8 etc. However, there are few studies on its evaluation of left ventricular diastolic function in APE patients, which deserves further study.…”
Section: Introductionmentioning
confidence: 84%
“…Patel et al [ 17 ] showed that the area under the ROC curve for parameters PFR, TPF, and 1/3FR measured by Myocardial Perfusion Imaging was 0.83, 0.75, and 0.80 for detecting LVEDP ≥ 18 mmHg, respectively, and that PFR, TPF, and 1/3FR were moderately correlated with LVEDP ( r = − 0.53, 0.45, − 0.45, P < 0.01). Zhang Fen et al [ 18 ]showed that good accuracy of LAVI, peak TR velocity, lateral e′, average e′, septal E/e′, and average E/e′ in diagnosing LVEDP elevation (AUC between 0.7 and 0.9). Previous studies have applied two examination methods to compare and evaluate LV systolic or diastolic function.…”
Section: Discussionmentioning
confidence: 99%